Analysis of Prices of Patented Medicines Listed In The National Formulary and E-Catalogue In Pusat Jantung Nasional (RSPJN) Harapan Kita Hospital, â€œDharmaisâ€ Cancer Hospital, and Pusat Otak Nasional Hospital (RSPON), Jakarta Province - Sari Mutiarani; Prih Sarnianto; Erna Kristin (Syntax Corporation, 2022)
Cost control of drugs plays an important role in the implementation of the Health Insurance Program and one of the efforts related to this is the through the drug selection process in National Formulary (Fornas) and the determination of drug prices in e-catalogue to obtain drugs, especially patented drugs, at affordable prices without reducing the quality of health service. This study aims to analyze the decline in drug prices during the patent period that listed in Fornas and e-catalogue and the savings in drugs costs during the patent period at the hospital and the factors that influence the decline in drug prices. In this descriptive study, secondary data was taken crosswise from the information management system in three special hospitals in Jakarta - RSPJN Harapan Kita,